Predictors of smoking cessation in smokers with chronic periodontitis: a 24-month study - Gislene INOUE; Ecinele Francisca ROSA; Elaine Fueta GOMES; Mariana Rocha GUGLIELMETTI; Priscila CORRAINI; Ricardo Koji TAKANO; Viviane Lé FERREIRA; Giuseppe Alexandre ROMITO; João Paulo Becker LOTUFO; Edinalva Tanajura Cruz SOUZA; Cláudio Mendes PANNUTI
Abstract The purpose of this 24-month study was to identify predictors of smoking cessation in a cohort of smokers with chronic periodontitis, attending a multidisciplinary smoking cessation program. Of the 286 subjects screened, 116 were included and received non-surgical periodontal treatment and smoking cessation therapy, which consisted of lectures, cognitive behavioral therapy, and pharmacotherapy, according to their individual needs. During initial periodontal treatment, dentists actively motivated the study subjects to stop smoking, using motivational interviewing techniques. Further smoking cessation counseling and support were also provided by the dentists, during periodontal maintenance sessions at 3, 6, 12 and 24 months of follow-up. Smoking status was assessed by means of a structured questionnaire, and was validated by exhaled carbon monoxide (CO) measurements. The Fagerström Test for Cigarette Dependence was used to assess smoking dependence. Of the 61 individuals that remained up to the 24-month examination, 31, 21 and 18 declared that they were not smoking at 3, 12 and 24 months, respectively. Smoking cessation after 24 months was associated with the male gender (OR = 3.77, 95%CI = 1.16-12.30), baseline CO levels less than 10ppm (OR = 5.81, 95%CI 1.76-19.23), not living or working with another smoker (OR = 7.38, 95%CI 1.76-30.98) and a lower mean Fagerström test score (OR = 5.63, 95%CI 1.55-20.43). We concluded that smoking cessation was associated with demographic, smoking history and cigarette dependence variables.